Study of direct bandgap type-I GeSn/GeSn double quantum well with improved carrier confinement. (20th September 2018) - Grant, Perry C; Margetis, Joe; Du, Wei; Zhou, Yiyin; Dou, Wei; Abernathy, Grey; Kuchuk, Andrian; Li, Baohua; Tolle, John; Liu, Jifeng; Sun, Greg; Soref, Richard A; et al.
Abstract: The GeSn-based quantum wells (QWs) have been investigated recently for the development of efficient GeSn emitters. Although our previous study indicated that the direct bandgap well with type-I band alignment was achieved, the demonstrated QW still has insufficient carrier confinement. In this work, we report the systematic study of light emission from the Ge0.91 Sn0.09 /Ge0.85 Sn0.15 /Ge0.91 Sn0.09 double QW structure. Two double QW samples, with the thicknesses of Ge0.85 Sn0.15 well of 6 and 19 nm, were investigated. Band structure calculations revealed that both samples feature type-I band alignment. Compared with our previous study, by increasing the Sn composition in GeSn barrier and well, the QW layer featured increased energy separation between the indirect and direct bandgaps towards a better direct gap semiconductor. Moreover, the thicker well sample exhibited improved carrier confinement compared to the thinner well sample due to lowered first quantized energy level in the Γ valley. To identify the optical transition characteristics, photoluminescence (PL) study using three pump lasers with different penetration depths and photon energies was performed. The PL spectra confirmed the direct bandgap well feature and the improved carrier confinement, as significantly enhanced QW emission from the thicker well sample was observed.